Electrosynthesis of nitrogen heterocycles using environmentally friendly methodologies - Chaminade, X. (2009)
Cyclic voltammetry and constant-current electrolysis in a one-compartment cell with a sacrificial anode has been used to study the indirect electroreduction of N-allyl- -haloamides by electrogenerated Ni(I) complexes conducted inN,N-dimethylformamide (DMF) and acetonitrile (ACN) and the resultswere compared with those obtained in protic solvents such as EtOH and EtOH–H2O mixtures. It was observed that the indirect electrochemical reduction of N-allyl- -haloamides led to the corresponding lactams and the yields and selectivities obtained in EtOH and EtOH–H2O were much better than those obtained in DMF or ACN.